Review of Atlanticus Scudder, 1894 (Orthoptera: Tettigoniidae: Tettigoniinae) from China, with description of 27 new species - Liu, Chun-Xiang (Zootaxa, 2013)
Atlanticus Scudder illustrates a disjunctive distribution comprising 1 subgenus and 10 valid species from eastern North America and 2 subgenera and 14 valid species from eastern Asia. Several authors also predicted that it would appear that China was rich in new species of the genus Atlanticus. Based on investigation of male stridulatory apparatus, as well as previously used characters, including male and female abdominal apex and measurements of various structures, we pres-ent a taxonomic account of 43 species of Atlanticus from China. Twenty-seven species of Atlanticus new to science are described. Erroneous synonyms are noted, based on examination of topotypes. Atlanticus changi Tinkham, 1941 and At-lanticus pieli Tinkham, 1941 are valid species and not synonyms of Atlanticus kiangsu Ramme, 1939. Atlanticus jeholen-sis Mori, 1935 is also valid and not a synonym of Atlanticus sinensis Uvarov, 1924. Moreover, the supposedly important character, i.e., length comparison between male pronotum and tegmen, is not suitable for differentiating two subgenera of Atlanticus, because it is easy to cause confusion. In contrast, the architecture of the male tegmen is a useful character to differentiate the two subgenera. The previous mentioned Species Groups and the corresponding descriptions are also stud-ied. Necessary illustrations are provided.